Respuesta :
[tex]\bf n^{th}\textit{ term of an arithmetic sequence}\\\\
a_n=a_1+(n-1)d\qquad
\begin{cases}
n=n^{th}\ term\\
a_1=\textit{first term's value}\\
d=\textit{common difference}
\end{cases}\\\\
-------------------------------\\\\[/tex]
[tex]\bf \begin{cases} f(n)=25\\ g(n)=3(n-1) \end{cases}\qquad \begin{array}{llll} f(n)+g(n)\implies &25+(n-1)&3\\ &\uparrow &\uparrow \\ &a_1&d \end{array}\\\\ -------------------------------\\\\ 12^{th}\textit{ term of an arithmetic sequence}\\\\ a_{12}=a_1+(12-1)d\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ d=\textit{common difference}\\ ----------\\ d=3\\ a_1=25\\ n=12 \end{cases} \\\\\\ a_{12}=25 + (12-1)3[/tex]
and fairly sure you know how much that is.
[tex]\bf \begin{cases} f(n)=25\\ g(n)=3(n-1) \end{cases}\qquad \begin{array}{llll} f(n)+g(n)\implies &25+(n-1)&3\\ &\uparrow &\uparrow \\ &a_1&d \end{array}\\\\ -------------------------------\\\\ 12^{th}\textit{ term of an arithmetic sequence}\\\\ a_{12}=a_1+(12-1)d\qquad \begin{cases} n=n^{th}\ term\\ a_1=\textit{first term's value}\\ d=\textit{common difference}\\ ----------\\ d=3\\ a_1=25\\ n=12 \end{cases} \\\\\\ a_{12}=25 + (12-1)3[/tex]
and fairly sure you know how much that is.
Answer with explanation:
Given functions : [tex]f(n)=25[/tex] and [tex]g(n)=3(n-1)[/tex]
When we combine then to create an arithmetic sequence [tex]A_n[/tex], we get
[tex]A_n=f(n)+g(n)\\\\\Rightarrow\ A_n=25+3(n-1)[/tex]
To solve for 12th term , we put n= 12 in [tex]A_n[/tex], we get
[tex]A_{12}=25+3(12-1)\\=25+3(11)\\=25+33=58[/tex]
Hence, the value of 12th term of [tex]A_n[/tex] = 58